Geotechnical Considerations for Longwall Top Coal Caving at Austar Coal Mine - Adrian L. Moodie (International Conference on Ground Control in Mining, 2011)
Austar Coal Mine (formerly Southlands and Ellalong Collieries) has had a long association with difficult strata control conditions associated with mining depth and a highly jointed/cleated coal seam. The conditions include poor longwall face conditions, cyclic loading, heavy tailgate (TG) roadway conditions, and difficulties in maintaining stable roadways on development at 5.2 m (17 ft), as well as the geotechnical challenges of an 8.5-m (27.9 ft) -wide roadway required for installation faces. The introduction of Longwall Top Coal Caving (LTCC) to this environment has aided in the management of some of these issues, but LTCC has also given rise to other geotechnical considerations. Additional geotechnical issues associated with LTCC not only require management during operations, but also require consideration when evaluating new mining areas at Austar Coal Mine or potential LTCC extractable resources throughout Australia and the world. In September 2006, LTCC commenced at Austar Coal Mine in longwall panel A1. Since this point the LTCC face has been increased from 147 to 216 m (482 to 709 ft)and finally to 227 m (745 ft) in width, and it has also been rehanded and modified in the three fully extracted panels to date. The application of LTCC in panels A1, A2, A3, and now A4 has been very successful, both from a coal resource recovery point of view and in the management of the principal hazards of spontaneous combustion and strata control. This paper focuses on the geotechnical aspects of the application of LTCC at Austar Coal Mine and also reviews some advances in general strata control management at the mine.